2018
DOI: 10.1021/acs.nanolett.8b01429
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Size-Tuned Graphene Oxide Frameworks as Ion-Selective and Protective Layers on Hydrocarbon Membranes for Vanadium Redox-Flow Batteries

Abstract: The laminated structure of graphene oxide (GO) membranes provides exceptional ion-separation properties due to the regular interlayer spacing ( d) between laminate layers. However, a larger effective pore size of the laminate immersed in water (∼11.1 Å) than the hydrated diameter of vanadium ions (>6.0 Å) prevents its use in vanadium redox-flow batteries (VRFB). In this work, we report an ion-selective graphene oxide framework (GOF) with a d tuned by cross-linking the GO nanosheets. Its effective pore size (∼5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 45 publications
1
80
0
Order By: Relevance
“…Well‐tuned channel size is also crucial to laminar membranes working as battery separators. It prevents the mixing of materials and electrolytes from positive and negative sides to sustain battery performance . In vanadium redox‐flow batteries (VRFB), an appropriate channel of 5.9 Å selectively permeates protons (<2.5 Å, main charge carriers) over VO 2+ (>6.0 Å), which minimizes the energy loss in cycling operations.…”
Section: Selective Performance and Future Designsmentioning
confidence: 99%
“…Well‐tuned channel size is also crucial to laminar membranes working as battery separators. It prevents the mixing of materials and electrolytes from positive and negative sides to sustain battery performance . In vanadium redox‐flow batteries (VRFB), an appropriate channel of 5.9 Å selectively permeates protons (<2.5 Å, main charge carriers) over VO 2+ (>6.0 Å), which minimizes the energy loss in cycling operations.…”
Section: Selective Performance and Future Designsmentioning
confidence: 99%
“…22,23 In addition, the chemical stability of these membranes is not good enough for long cycle life in practice. 24 To overcome this problem, semi interpenetrating polymer network (semi-IPN) has been developed. It is a facile and efficient approach to increase the stability of IEMs without losing their proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The tailored SPVDF-co-HFP membranes exhibited lesser IEC of 0.95% at 0.75 wt% of PEI-RGO probably due to the strong acid-base pair formation between the amine and sulfonic acid groups confine the dissociable H + ions. 10,25 3.2.6 | Proton conductivity Table 2 depicts the proton conductivity of bare and tailored mem-…”
Section: Water Uptake Swelling Ratio and Iecmentioning
confidence: 99%
“…9 Kim et al optimized the pore size of ion-selective GO framework (GOF) via tuning the interlayer spacing (d) between the sandwiched layers by cross-linking and developed GOF/sulfonated poly(arylene ether sulfone) (SPAES) membranes with high energy efficiency and low vanadium-ion permeability. 10 Highly stable styrene divinylbenzene co-polymer membrane incorporated with sulfonated graphene oxide (SGO) additive is developed by Rajput et al and found that low vanadium-ion permeability and adequate proton conductivity. 11 The blend membranes are also developed using acid-base pair interaction with the aim of improvement in proton conductivity and reduction in vanadium-ion permeability as well as swelling ratio.…”
Section: Introductionmentioning
confidence: 99%